Electron Crystallography - Singh, Devinder; Condurache-Bota, Simona; Singh, Devinder; Condurache-Bota, Simona (IntechOpen, 2020)
In the quantitative determination of new structures, micro-/nano-crystalline materials pose significant challenges. The different properties of materials are structure-dependent. Traditionally, X-ray crystallography has been used for the analysis of these materials. Electron diffraction is a technique that complements other techniques; for example, single crystal X-ray diffraction and powder X-ray diffraction for determination of structure. Electron diffraction plays a very important role when crystals are very small using single crystal X-ray diffraction or very complex for structure solution by powder X-ray diffraction. With the introduction of advanced methodologies, important methods for crystal structural analysis in the field of electron crystallography have been discovered, such as rotation electron diffraction (RED) and automated electron diffraction tomography (ADT). In recent years, large numbers of crystal structures have been solved using electron crystallography.
English
Keywords: Spectrum analysis, spectrochemistry, mass spectrometry; Crystallography